ANALISIS KERUSAKAN POHON DI HUTAN KOTA STADION KOTA METRO PROVINSI LAMPUNG - Bondan Abimanyu; Wahyu Hidayat; Rahmat Safe'i (JURNAL HUTAN PULAU-PULAU KECIL, 2019)
Urban forest is one component of green open space. The assessment of the condition of tree damage in the area of ​​green open space is very important. Damage to trees can eliminate the function of the tree itself, it can even cause economic losses. Therefore, tree damage can be an indicator where trees are said to be healthy or sick. This study aims to determine the status of the condition of tree damage in the Stadion Urban Forest, Metro City, Lampung Province. The study was conducted using the Forest Health Monitoring (FHM) method. The results showed that there were eight locations of tree damage with the most found locations of damage, namely at the branch location (code 7) as many as 115 locations (37.34%); 12 types of tree damage with the most types of damage found, namely the type of broken or dead branches (code 22) as many as 110 (35.71%); with an average severity of tree damage ≥20%. Thus the status of the condition of tree damage in the Stadion Urban Forest, Metro City, Lampung Province is in the healthy category of 300 trees (77%), is being 69 trees (18%), and sick 19 trees (5%).